The exposure metric: does including time since exposure in the calculation of working lifetime exposure provide a better understanding of disease risk than the cumulative exposure? / La dose cumulativa di esposizione a silice: è possibile una descrizione più accurata del rischio associato inserendo gli anni trascorsi dall’esposizione nel calcolo dell’esposizione cumulativa? - Rice, C.; Jin, N.; Cocco et al., P. (La Medicina del Lavoro, 2011)
SummaryBackground: When exposure measurements are available for occupational epidemiology studies, the cumulative exposure (the sum of the products of duration and exposure intensity at all jobs) is generally selected as the summary metric for chronic diseases. For silica exposures, a metric that weights each exposure by the number of years since it occurred has been suggested as more biologically relevant. Comparative reports of analyses using both metrics have not been found in the literature, however. Methods: We calculated both metrics for silica exposure, and evaluated exposure-response relations for lung cancer and silicosis in two separate case-control studies. Results: Generally the results were consistent, due to the high correlation between the two metrics and the fact that the rate of time away from work during the employment years was low. Conclusion: The significant relation between exposure and silicosis using the weighted metric provides additional point estimates of risk, adding to the understanding of exposure-response.